DNA dynamics in complex coacervate droplets and micelles. Issue 10 (22nd February 2022) - Bos, Inge; Brink, Eline; Michels, Lucile; Sprakel, Joris
Abstract : DNA can be mixed with oppositely charged homopolymers or diblock copolymers to form respectively complex coacervate droplets or complex coacervate core micelles. We study the chain length effect on the dynamics of these complex coacervate structures. Abstract : Single stranded DNA (ssDNA), or another polyanion, can be mixed with polycations to form liquid-like complex coacervates. When the polycations are replaced by cationic–neutral diblock copolymers, complex coacervate core micelles (C3Ms) can be formed instead. In both complex coacervates and C3Ms, dynamics plays an important role. Yet, to date, the effect of chain length on the dynamics effect is still not fully understood. The DNA complexes provide a versatile platform to further elucidate these chain length effects because the DNA is monodisperse and its length can be easily adapted. Therefore, we study in this paper the dynamics of fluorescently labelled ssDNA in both complex coacervate droplets and micelles. The DNA dynamics in the complex coacervate droplets is probed by fluorescence recovery after photobleaching (FRAP). We observe that the DNA diffusion coefficient depends more strongly on the DNA length than predicted by the sticky Rouse model and we show that this can be partly explained by changes in complex coacervate density, but that also other factors might play a role. We measure the molecular exchange of C3Ms by making use of Förster resonance energy transfer (FRET) and complement these measurements with Langevin dynamics simulations. We conclude that chain length polydispersity is the main cause of a broad distribution of exchange rates. We hypothesise that the different exchange rates that we observe for the monodisperse DNA are mainly caused by differences in dye interactions and show that the dye can indeed have a large effect on the C3M exchange. In addition, we show that a new description of the C3M molecular exchange is required that accounts among others for the effect of the length of the oppositely charged core species. Together our findings can help to better understand the dynamics in both specific DNA systems and in complex coacervate droplets and micelles in general.